APLIKASI MONITORING KEBUTUHAN KONSUMSI AIR PUTIH HARIAN BERBASIS ANDROID MENGGUNAKAN IONIC DAN LARAVEL PADA RANCANG BANGUN SMART BOTTLE - Arminditya Fajri Akbar; Prihatin Oktivasari (Politeknik Negeri Jakarta, 2017)
ABSTRACTNearly half of Indonesia's population has dehydration. THIRST Research (2009) proves that Indonesian people is still low awareness of drinking water. Consuming enough water could be one way to prevent dehydration. Smart Bottle application is able to provide amount of daily water needs based on user profile that entered when registering account. The problem in the calculation of water consumption can be overcome by using the data of the waterflow sensor calculation. Implementation result of Smart Bottle application has proved that the water needs of each person can be known, the water that has been consumed can be calculated automatically, and push notification can be able to give reminder about water drinking to Smart Bottle users during their busy. In this paper, hybrid application for android has implemented using Ionic Framework and Laravel, then push notification using Firebase Cloud Messaging.Keywords : Daily water needs, Firebase Cloud Messaging, hybrid application, water consumed calculation, waterflow sensorABSTRAKNearly half of Indonesia's population has dehydration. THIRST Research (2009) proves that Indonesian people is still low awareness of drinking water. Consuming enough water could be one way to prevent dehydration. Smart Bottle application is able to provide amount of daily water needs based on user profile that entered when registering account. The problem in the calculation of water consumption can be overcome by using the data of the waterflow sensor calculation. Implementation result of Smart Bottle application has proved that the water needs of each person can be known, the water that has been consumed can be calculated automatically, and push notification can be able to give reminder about water drinking to Smart Bottle users during their busy. In this paper, hybrid application for android has implemented using Ionic Framework and Laravel, then push notification using Firebase Cloud Messaging.Keywords : Daily water needs, Firebase Cloud Messaging, hybrid application, water consumed calculation, waterflow sensor